Nanowarming using Au-tipped Co35Fe65 ferromagnetic nanowires. Issue 31 (9th July 2019) - Shore, Daniel; Ghemes, Adrian; Dragos-Pinzaru, Oana; Gao, Zhe; Shao, Qi; Sharma, Anirudh; Um, Joseph; Tabakovic, Ibro; Bischof, John C.; Stadler, Bethanie J. H.
Abstract : When placed in an AC magnetic field, magnetic nanowires enable uniform nanowarming of cryopreservation agents 20× faster than the critical warming rate required to prevent devitrification. Abstract : Ferromagnetic Co35 Fe65, Fe, Co, and Ni nanowires have high saturation magnetizations ( M s ) and magnetic anisotropies, making them ideal for magnetic heating in an alternating magnetic field (AMF). Here, Au-tipped nanowires were coated with polyethylene glycol (PEG) and specific absorption rates (SAR) were measured in glycerol. SAR increased when using metals with increasing M s (Co35 Fe65 > Fe > Co > Ni), reaching 1610 ± 20 W g −1 metal at 1 mg metal per ml glycerol for Co35 Fe65 nanowires using 190 kHz and 20 kA m −1 . Aligning these nanowires parallel to the AMF increased SAR up to 2010 W g −1 Co35 Fe65 . Next, Co35 Fe65 nanowires were used to nanowarm vitrified VS55, a common cryoprotective agent (CPA).Nanowarming rates up to 1000 °C min −1 (5 mg Co35 Fe65 per ml VS55) were achieved, which is 20× faster than the critical warming rate (50 °C min −1 ) for VS55 and other common CPAs. Human dermal fibroblast cells exposed to VS55, and Co35 Fe65 nanowire concentrations of 0, 1 and 2.5 mg Fe per ml all showed similar cell viability, indicating that the nanowires had minimal cytotoxicity. With the ability to provide rapid and uniform heating, ferromagnetic nanowires have excellent potential for nanowarming cryopreserved tissues.